USO MISTO DO SOLO: ASSOCIAÇÃO ENTRE A MEDIDA DE INTEGRAÇÃO E O CÁLCULO DE ENTROPIA UM ESTUDO DE CASO - Olak, Andre; Favarão, Ana Luiza; Kanashiro, Milena (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Space Syntax theory, initiated by Hillier and Hanson at University College London in the 1970's, seeks to study urban design and their respective correspondences such as location of commercial activities and pedestrian movement. Likewise, locational theories, advent from marketing and economics, seeks to identify characteristics that encourage the localization of commercial activities in cities, such as the flow of people. Considering that Spatial Syntax theories suggest that the configuration of streets can influence the movement of pedestrians and that for locational theories this is fundamental in locating commercial activities, the research seeks to verify in an empirical case study if urban design correlates with the location business activities. For this, integration measures of spatial syntax and urban entropy were calculated and compared using the Pearson correlation method. The evidences found shows correlation between the variables and suggest which integration ranges is more correlated with commercial activities. It is hoped that this study may contribute to a better understanding of the phenomenon of land use specialization, especially in medium and small cities, as representative of most Brazilian cities.